Diagnostic challenge of large congenital liver cyst in the newborn. Issue 2 (April 2014) - Viswanathan, Sreekanth; Kumar, Deepak
Abstract Liver cysts in the newborn often pose significant diagnostic challenges. Described herein is a case of large congenital liver cyst that was difficult to diagnose both antenatally and postnatally and which was later diagnosed as Caroli disease.